Novel molecular adducts of an anti-cancer drug vandetanib with enhanced solubility - Bandaru, Ravi Kumar; Giri, Lopamudra; Krishna, Gamidi Rama; Dandela, Rambabu (Crystengcomm, 2024)
The solubility, permeability, and dissolution rate of an active pharmaceutical ingredient (API) are critical factors in determining its pharmacokinetic performance in oral dosage forms. Modifying these properties can potentially enhance the drug's pharmacokinetics. Vandetanib (VDTB), classified as a class II anti-cancer drug in the biopharmaceutical classification system (BCS), suffers from low solubility (0.008 mg mL-1) and an extended pharmacokinetic half-life (19 days), necessitating the administration of high doses, which leads to undesirable side effects. To address this issue, we have employed a crystal engineering approach to enhance the solubility of VDTB. We employed the liquid-assisted grinding (LAG) method followed by the slow evaporation technique to prepare novel solid forms of VDTB by incorporating various aliphatic dicarboxylic acids, including succinic acid (SUA), adipic acid (ADA), pimelic acid (PIA), azelaic acid (AZA), and sebacic acid (SBA). These newly obtained solid forms were characterized by SC-XRD, PXRD, TGA, and DSC experiments. The crystal structure analyses revealed a proton transfer between the carboxylic acid group of aliphatic acids and the N-methyl piperidine moiety of VDTB, confirming salt/adduct formation. Additionally, all of the molecular salts were stabilized by charge-assisted N+-HMIDLINE HORIZONTAL ELLIPSISO- hydrogen bonds, while the parent VDTB crystal structure is stabilised by N-HMIDLINE HORIZONTAL ELLIPSISN interactions. Moreover, the solubility and dissolution rate of these new solid forms were assessed in a pH 7.4 phosphate buffer medium, with the results indicating that all of the solid forms, except for VDTB:SBA, exhibited higher solubility compared to pure VDTB. These findings offer promising prospects for the development of an improved VDTB formulation with enhanced pharmacokinetic properties. Successful attempt to improve the solubility and dissolution rate of Vandetanib - an anti-cancer drug, by crystal engineering approach.
Keywords: Amorfization; hydrate; Parameters; Salt; Thyroid-Cancer